Mobile colistin resistance gene mcr-1 detected on an IncI1 plasmid in Escherichia coli from meat. (December 2020) - Brouwer, Michael S.M.; Goodman, Richard N.; Kant, Arie; Mevius, Dik; Newire, Enas; Roberts, Adam P.; Veldman, Kees T.
Highlights: The mcr-1 gene was identified for the first time on an IncI1 plasmid. The plasmid was present in a commensal Escherichia coli from livestock. The IncI1 plasmid was genetically distinct from resistance-encoding IncI1 plasmids previously isolated in the Netherlands. mcr-1 was flanked by two copies of IS Apl1, which are likely responsible for its insertion. The plasmid was conjugative between E. coli strains under laboratory conditions. Abstract: Objectives: Mobile colistin resistance ( mcr ) genes encoded on conjugative plasmids, although described only relatively recently, have been reported globally both in humans and livestock. The genes are often associated with the insertion sequence IS Apl1 that can transpose the genes to novel genetic locations. Since its first report, multiple variants of mcr have been discovered in a variety of genetic locations in Escherichia coli, in plasmids and integrated into the chromosome. Methods: Using hybrid assembly of short-read and long-read whole-genome sequencing data, the presence of mcr-1 was confirmed on an IncI1 plasmid in E. coli . In vitro conjugation assays were performed to determine the potential to transfer between strains. Genetic comparison with previously reported IncI1 plasmids was performed. Results: The genomic sequence identified that mcr-1 is present on a complete IncI1 plasmid. Comparison with previously reported extended-spectrum β-lactamase (ESBL)-encoding plasmids from E. coli in the Netherlands from the same time period indicated a distinct lineage for this plasmid. Conclusions: The observation of mcr-1 on an IncI1 plasmid confirms that the genetic region of this gene is actively transposed between genetic locations. This active transposition has consequences for the study of the epidemiology of mcr in populations.